Development of the Godorboy Game Model in Physical Education Learning for Elementary School Students - Agimis Akbar Nur Salam; Agus Pujianto (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
This research aims to develop a suitable, practical, and effective Godorboy game model for use in physical education lessons for grade five elementary school students. This research uses a Research and Development (R&D) approach by applying the ADDIE model, which consists of the Analysis, Design, Development, Implementation, and Evaluation stages. The product is validated by experts and tested through small-scale and large-scale trials. The small-scale trial involved 30 students, while the large-scale trial involved 73 students from two schools. Data were collected through questionnaires, observations, and documentation, and analyzed using percentage techniques. The results show that expert validation reaches 97.5% (the category is very appropriate). Small-scale trials reached 78.2% (good category), while large-scale trials reached 97.6% and 95.8% (very good category). These findings suggest that Godorboy's game model is feasible, practical, and effective in increasing student participation and engagement. Therefore, this model can be utilized as an alternative strategy in physical education.